2017
DOI: 10.1016/j.ffa.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A complete characterization of Galois subfields of the generalized Giulietti–Korchmáros function field

Abstract: We give a complete characterization of all Galois subfields of the generalized GiuliettiKorchmáros function fields Cn/F q 2n for n ≥ 5. Calculating the genera of the corresponding fixed fields, we find new additions to the list of known genera of maximal function fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…2 6 G = Sym(3) = α ⋊ β , α of type (B2), β of type (A). 1 8 G = C 4 × C 2 = α × β , α of type (A), β of type (A). 0 7 G = C 7 = σ , σ of type (C).…”
Section: Further Resultsmentioning
confidence: 99%
“…2 6 G = Sym(3) = α ⋊ β , α of type (B2), β of type (A). 1 8 G = C 4 × C 2 = α × β , α of type (A), β of type (A). 0 7 G = C 7 = σ , σ of type (C).…”
Section: Further Resultsmentioning
confidence: 99%
“…By Remark 3.2, H = M ∩ PSU(3, q) M and [M : H] = 3. Arguing as in the proof of Proposition 3.8 it can be shown that M/Ker(ϕ) is isomorphic to a subgroup of PΓL (2,9), where ϕ is the action by conjugation of M on H; H commutes elementwise with an element of order 3 in M \ H; H is contained either in M 2 or in M 3 or in M 4 as described in Theorem 3.1, a contradiction to Theorem 2.1.…”
Section: 5mentioning
confidence: 92%
“…Also, A 6 M since A 6 is characteristic in H. Hence, M/Ker(ϕ) is isomorphic to an automorphism group of A 6 , where Ker(ϕ) is the kernel of the action by conjugation of M on A 6 . As A 6 ∼ = PSL(2, 9), M/Ker(ϕ) is isomorphic to a subgroup of PΓL (2,9). Since the largest subgroup of P ΓL(2, 9) has order 720 and the order of M/Ker(ϕ) is at least |H| = 720, we have |Ker(ϕ)| = 3.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…We have indicated a genus with boldface if it gives a new addition to the genus spectrum of Fq2n‐maximal curves. To check whether or not a genus gave a new addition, we compared our results with the genera of maximal function fields given in . q=4 and n=5: {32,156,302,1506,1532}, q=4 and n=7: {212,842,1056,4206,24572}, q=5 and n=5: {6242,12484,18724}, q=7 and n=5: {243,485,969,1941,4563,9125,18249,36501,50403,100805,201609}. …”
Section: Determination Of the Full Automorphism Group Of Xn N⩾5mentioning
confidence: 99%